Brothers of Crab / Fairol Japar … [et al.] - Japar, Fairol; Harun, Hannan; Ismail, Mohd Hafiz; Ramli, Muhamad Helmi; Jamaluddin, Mohd Zaidy (2007)
Brothers of Crab is an agricultural food production company aimed to be the main producer and supplier of Soft Shell and Hard Shell Mud Crabs. To be a leader in crab production, a synergistic collaboration must be maintained between the company and the government through conjoined efforts of improving production level and technology. Systematic development based on Research and Development (R&D) from the government and developed technologies adapted will be sustainable and thus benefits all for generations to come.